1977
DOI: 10.2307/1935601
|View full text |Cite
|
Sign up to set email alerts
|

Acclimatization of Thermoregulation in Desert‐Inhabiting Jackrabbits(Lepus Alleni and Lepus Californicus

Abstract: Seasonal physiological responses to ambient temperature were determined for the black‐tailed jackrabbit, Lepus californicus and the antelope jackrabbit, Lepus alieni at Tucson, Arizona. Both species exhibited similar responses to changes in season although differences were noted. From winter to summer the thermoneutral zone shifted upwards, with the shift occurring at both critical temperatures in L. californicus and at only the lower critical temperature in L. alieni. Standard metabolism above thermoneutralit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…A precedent for a seasonal change in the effects of wind is provided by data on pelage insulation in the black-tailed jackrabbit Lepus californicus. The difference in insulation found in this mammal between summer and winter (Hinds 1977) is substantially magnified by the effects of wind (Harris et al 1985). A seasonal shift in heat loss due to the combined effects of cold and wind could be of particular significance during flight.…”
Section: Seasonal Changes In Plumage Insulationmentioning
confidence: 88%
“…A precedent for a seasonal change in the effects of wind is provided by data on pelage insulation in the black-tailed jackrabbit Lepus californicus. The difference in insulation found in this mammal between summer and winter (Hinds 1977) is substantially magnified by the effects of wind (Harris et al 1985). A seasonal shift in heat loss due to the combined effects of cold and wind could be of particular significance during flight.…”
Section: Seasonal Changes In Plumage Insulationmentioning
confidence: 88%
“…Lepus californicus is also more cold tolerant, forms of the species occurring in the Great Basin and Great Plains, while L. alleni is confined to habitats having annual temperatures >15.4°C with <60 mean days a year below freezing. Hinds (1977) noted that L. alleni went into hypothermia when body temperatures dropped to 28ºC.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pinna of leporids at rest is a thermoregulatory organ (Schmidt-Nielsen et al, 1965;Dawson and Schmidt-Nielsen, 1966;Hinds, 1977;Marai et al, 2005), we have demonstrated that the size of the pinna in this species is not determined by the requirements of sedentary diurnal thermoregulation. The pinna of the Australian population of the hare, unlike that of the European rabbit (Parer and Libke, 1985), had not increased in length relative to its English antecedents (Fig.…”
Section: Thermoregulationmentioning
confidence: 43%
“…The pinna reaches its most extreme sizes in the genus Lepus. Schmidt-Nielsen et al (1965), Dawson and Schmidt-Nielsen (1966), and Hinds (1977) concluded that the large sizes of the pinnae of two North American species, Lepus alleni and Lepus californicus, were determined by the need for radiant heat loss under the thermal loads prevalent in summers in the south-west of the United States of America (e.g. mean July maximum for Las Vegas, NM: 28.68C).…”
Section: Introductionmentioning
confidence: 99%